Toxicity Evaluation of Graphene Oxide and Titania Loaded Nafion Membranes in Zebrafish - Pecoraro, Roberta; D'Angelo, Daniele; Filice, Simona; Scalese, Silvia; Capparucci, Fabiano; Marino, Fabio; Iaria, Carmelo; Guerriero, Giulia; Tibullo, Daniele; Scalisi, Elena M.; Salvaggio, Antonio; Nicotera, Isabella; et al. (Frontiers in Physiology, 2018)
The use of nanomaterials in several application fields has received in the last decades a great attention due to their peculiar properties, but also raised many doubts about possible toxicity when these materials are used for some specific applications, such as water purification. Indeed a careful investigation is needed in order to exclude possible harmful side effects related to the use of nanotechnology. The effect that the nanoparticles may have on the marine organisms depends on their size, chemical composition, surface structure, solubility, shape and how the individual nanoparticles aggregate together. In order to make the most of their potential, without polluting the environment, many researchers are trying to trap them into some kind of matrix that keeps them active but avoids their dispersion in the environment. In this study we have tested nanocomposite membranes prepared using Nafion polymer combined with various fillers, such as anatase-type TiO2 nanoparticles and graphene oxide. The non-toxicity of these nanocomposites, already shown to be effective for water purification applications in our previous studies, was recognized by testing the effect of tDahe different materials on zebrafish embryos. Zebrafish was considered an excellent model for ecotoxicological studies andfor this reason zebrafish embryos were exposed to different concentrations of free nanoparticles and to the nanocomposite membranes. As biomarkers of exposure, we evaluated the expression of heme-oxygenase 1 and inducible Nitric Oxide Synthases by immunohistochemistry and gene expression. Embryo toxicity test showed that neither mortality nor sublethal effects were caused by the different nanoparticles and nano-systems tested. Only zebrafish larvae exposed to free nanoparticles have shown a different response to antibodies anti-heme-oxygenase 1 and anti- inducible Nitric Oxide Synthases. The immunolocalization analysis in fact has highlighted an increase in the synthesis of these biomarkers.